Exploring the role of personal and job resources in professional satisfaction: the case of the hotel sector in Algarve. Issue 1 (15th September 2021) - Viseu, João; Pinto, Patrícia; Borralha, Sérgio da; Jesus, Saúl Neves de
Abstract : Purpose: This study aims to follow the Job Demands-Resources model to understand how: job resources (organisational health and organisational support) were related to work engagement through intrinsic motivation (personal resource); and intrinsic motivation was associated with job satisfaction through work engagement. Design/methodology/approach: Data were collected from 504 workers (50% women and 50% men; M = 39.48 years old, SD = 11.98) at four- and five-star hotels from the Algarve, Portugal. Through structural equation modelling, using the maximum likelihood estimation method, nine research hypotheses were tested. Findings: Results indicated that intrinsic motivation mediated the relationship between organisational health and work engagement. Work engagement mediated the association between intrinsic motivation and job satisfaction. Practical implications: Hotel managers must promote a supportive work environment and demonstrate openness to receiving suggestions from employees. Employees should also be informed about their hotel's business model and operation. At the task design level, challenging and stimulating tasks should be created and job rotation policies should be implemented to foster work motivation. Also, managers must recruit employees that present positive emotions, proactivity and stress and time management skills. Originality/value: This study considered the role of organisational health as a job resource, a new concept in hospitality. The selected personal resource, intrinsic motivation, is different from positive psychological capital, the typical resource used in hospitality studies.